Sorption of Hydrogen on Sponge Titanium - VASUT, FELICIA; PREDA, ANISOARA; STEFANESCU, IOAN; ZAMFIRACHE, MARIUS; DAVID, CLAUDIA (Asian Journal of Chemistry, 2010)
To build a detritiation facility for heavy water that has been used as moderator and cooling agent in the CANDU reactor from Cernavoda, Romania is necessary to have in place a storage vessel to deposit the hydrogen isotopes, especially tritium. In preparation for the design of the storage vessel, sponge titanium and hydrogen gas were used during experiments as storage material and gas to be stored, respectively. The presence of tritium was simulated by mixing helium into the hydrogen. During the adsorption process, several parameters may affect the titanium adsorption capacity and the hydrogen adsorption rate such as metal activation temperature, gas pressure, helium content, etc. The present paper presents the influence of these parameters on the metallic titanium hydrogenation reaction.